2017
DOI: 10.1111/jocn.13766
|View full text |Cite
|
Sign up to set email alerts
|

Compassion fatigue in nurses: A metasynthesis

Abstract: Aims and objectives: To interpret the body of qualitative work focusing on compassion fatigue to distil a common understanding that could then be applied to nursing care.Background: Complex demands place extraordinary stress on nurses struggling to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
170
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(200 citation statements)
references
References 80 publications
(145 reference statements)
6
170
1
7
Order By: Relevance
“…This maximum hours worked per week regulation avoids the overtime and broken shift work that is so often a major contributing factor to CF; 12 h shifts mean more time away in larger blocks from the workplace. This is unlike other jurisdictions, where hours are not so regulated by the state and BO is a major casual contributor factor to CF (Nolte, Downing, Ternane, & Hastings‐Tolsma, ).…”
Section: Discussionmentioning
confidence: 91%
“…This maximum hours worked per week regulation avoids the overtime and broken shift work that is so often a major contributing factor to CF; 12 h shifts mean more time away in larger blocks from the workplace. This is unlike other jurisdictions, where hours are not so regulated by the state and BO is a major casual contributor factor to CF (Nolte, Downing, Ternane, & Hastings‐Tolsma, ).…”
Section: Discussionmentioning
confidence: 91%
“…Once CF is experienced, there is no hope for recovery due to the complete depletion of compassionate energy . Previous concept analyses and other published works on CF in nursing identified an array of physical, emotional, and spiritual manifestations that defined the concept, with the element of exhaustion or decline in energy and lack of empathetic ability being the most common elements . Physical and emotional symptoms of CF were also described metaphorically as “’just plain worn out’ and ’walking on a tight rope’.” , pp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bao and Taliaferro found that the use of psychological capital can eliminate and prevent self‐reported CF while enhancing quality patient care at the same time. Psychological capital encompassed four dimensions that included “self‐efficacy, optimism, hope, and resiliency.” p. 36 It was also suggested that enhancing knowledge about CF could be protective …”
Section: Literature Reviewmentioning
confidence: 99%
“…Although, it should be noted that nurses having the most career have little approach in daily life in hospitals. They may feel compassion fatigue (Joinson, ; Nolte, Downing, Temane, & Hastings‐Tolsma, ) because it is very stressful to care children with life‐threatening conditions and their families with ambivalent feelings. In order to care themselves, it also seemed to be important to communicate and share nurses' feelings with each other timely and have opportunity for grief care for health care providers.…”
Section: Discussionmentioning
confidence: 99%